2010
DOI: 10.1371/journal.pone.0010046
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Determination of Fluctuating Forces during Endosome Trafficking Using a Combination of Active and Passive Microrheology

Abstract: BackgroundRegulation of intracellular trafficking is a central issue in cell biology. The forces acting on intracellular vesicles (endosomes) can be assessed in living cells by using a combination of active and passive microrheology.Methodology/Principal FindingsThis dual approach is based on endosome labeling with magnetic nanoparticles. The resulting magnetic endosomes act both as probes that can be manipulated with external magnetic fields to infer the viscoelastic modulus of their surrounding microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
124
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 42 publications
16
124
0
Order By: Relevance
“…This is not necessarily a drawback, as these symmetric bimodal distributions have never been clearly evidenced experimentally. Still, the stochastic model reproduces well that the tug-of-war leads to anomalous diffusion in agreement with some experimental observations [213,68,308,318]. Indeed, at very short time scales and if thermal fluctuations are taken into account, subdiffusion is observed as a result of the trapping of the cargo by oppositely pulling motors [193].…”
Section: Tug-of-warsupporting
confidence: 88%
“…This is not necessarily a drawback, as these symmetric bimodal distributions have never been clearly evidenced experimentally. Still, the stochastic model reproduces well that the tug-of-war leads to anomalous diffusion in agreement with some experimental observations [213,68,308,318]. Indeed, at very short time scales and if thermal fluctuations are taken into account, subdiffusion is observed as a result of the trapping of the cargo by oppositely pulling motors [193].…”
Section: Tug-of-warsupporting
confidence: 88%
“…Furthermore, if thermal fluctuations are not the only driving force for intracellular motion, then the application of equilibrium theories, such as the Stokes-Einstein equation, to biological processes may not be valid. Indeed, several studies have demonstrated that the fluctuation-dissipation theorem is violated in vivo (4,5,7,8,42). These exciting findings may fundamentally change how we think about cellular processes and the nature of the cytoplasm (36).…”
Section: Discussionmentioning
confidence: 99%
“…External cell measurements have been used to apply deformations and to measure local CSK and PM responses as well as whole cell mechanics. For example, methods such as atomic force microscopy [22,23] , magnetic [24,25] and laser tweezers [26,27] , have been used to apply forces at specific sites on the PM, inducing direct changes to the underlying actin CSK and revealing local PM dynamics and response to deformations. Whole cell stretching has been applied to adherent cells in two general approaches: those requiring cells to be suspended in solution [28] , and those where cells are adhered on a typically deformable substrate [9,10,[29][30][31][32][33] .…”
Section: Applying and Estimating Dynamic Deformations And Responses Omentioning
confidence: 99%